2023
DOI: 10.54183/jssr.v3i1.141
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Students’ Cognitive and Emotional Engagement on Students’ Academic Success and Academic Productivity

Abstract: This paper investigates the effect of students’ cognitive and emotional engagement on learning achievement in government primary male schools. Academic achievement was assessed through academic success and academic productivity. Data were gathered and utilized a survey questionnaire with 120 male primary school teachers as the sample. Descriptive Statistics and Pearson correlation were used to assess the data that had been obtained. Analysis of the data revealed a strong positive correlation between student co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Digital transformation in education is a revolution that has the potential to change the way students learn and the way educators teach. This involves technology integration [81], [82], data analysis [83], [84], and online learning platforms [85], [86] into traditional educational practices. Digital tools and resources enable personalized learning experiences, increased access to educational materials, and real-time assessment of student progress.…”
Section: Resultsmentioning
confidence: 99%
“…Digital transformation in education is a revolution that has the potential to change the way students learn and the way educators teach. This involves technology integration [81], [82], data analysis [83], [84], and online learning platforms [85], [86] into traditional educational practices. Digital tools and resources enable personalized learning experiences, increased access to educational materials, and real-time assessment of student progress.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous authors observed that students in technical careers and vocational training programs require spatial skills to succeed academically in Technical Drawing subjects [20,[28][29][30][31][32]. Saorín-Pérez et al [18], in addition to confirming this relationship specifically in engineering degrees, found that studying Technical Drawing improves mental rotation skills [33], while other studies also highlight its positive effects on learning in other engineering subjects [24,34]. In summary, Technical Drawing is closely linked to spatial skills and holds significant relevance in both engineering studies and professional fields.…”
Section: Spatial Skills In Engineering Studies and In Graphical Expre...mentioning
confidence: 97%
“…As a result, there are less conflicts and greater disputes-tolerance for diversity. Academic achievement is one of the major factors considered by employers in achievement of workers especially for fresh graduates (Khan, Gul, & Zeb, 2023). Proper education improves people's understanding of the world around them, making them less susceptible to the influence of others.…”
Section: Introductionmentioning
confidence: 99%
“…They found that habits of taking notes and writing back class materials significantly affected the academic performance of the students. (Khan et al, 2023) investigated strong positive correlation between student cognitive engagement with and academic success and academic productivity.…”
mentioning
confidence: 99%